Coffee Shop Marketing Strategy Using SWOT Analysis to Increase Business Competitiveness - Hery Purnomo; Rully Arifiansyah; Nur Andini Sudirman; Ilma Wulansari Hasdiansa; Sitti Hasbiah (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
This study aims to assess and analyze whether the marketing strategy carried out by a Coffee Shop called Safehaus for approximately two years (2022-2023) can increase competitiveness. This type of research is descriptive qualitative. The population in this study were the owner and all employees as many as 13 respondents using saturated sampling, which is a sampling technique when all members of the population are used as samples. Data collection techniques were carried out by conducting interviews and questionnaires. While the data analysis technique used is to use SWOT analysis (Strength, Weakness, Oppotunities and Threats) and use the IFAS and EFAS tables. Based on the results of this study, it shows that Coffee Shop is in the first quadrant, namely supporting a growth strategy, this result is very beneficial for the company in increasing its competitiveness because it supports aggressive growth (growth oriented strategy). A business that is in the first quadrant condition is very profitable because it has strengths and can take advantage of opportunities well so that it can make it possible to expand, and achieve maximum progress.